Detoksifikasi Aluminium dan Ketersediaan Fosforus dalam Tanah Masam Melalui Aplikasi Bahan Organik - Lilik Tri Indriyati; Budi Nugroho; Fahrizal Hazra (Institut Pertanian Bogor, 2023)
Organic matter that is usually quite widely available around farmers' land can be one of the solutions in overcoming the problem of soil acidification and nutrient deficiencies in tropical highly weathered soils. However, one of the main problems in utilizing such organic matter on acidic soils is the diversity of its chemical composition, which affects the decomposition of the organic matter. In this study, a mixture of soil with five types of organic matter was incubated, namely cow manure, chicken manure, rice straw, legume plant residue, and their combination, with doses equivalent to 0, 7.5 and 15 tons/ha. Mixtures of soil with organic matter were incubated for 120 days under conditions of field capacity moisture. The aim was to evaluate the amelioration effect of the organic matter on soil acidification (exchangeable-Al and soil pH), available P, and phosphatase activity. The application of organic matter type and dose has a marked effect on decreasing the content of exchangeable Al and increasing soil pH, P-available, and phosphatase activity. Chicken manure application showed the best effect in lowering soil exchangeable-Al and increasing pH, available-P, and phosphatase activity. Keywords: amelioration, manure, phosphatase